Culture, wellbeing, and the Living Standards Framework: A perspective - Paul Dalziel; Caroline Saunders; Catherine Savage (New Zealand Government, The Treasury, 2019)
This Discussion Paper provides a perspective on how to better reflect culture in the Living Standards Framework (LSF). It was jointly commissioned by the Treasury and Manatu Taonga Ministry for Culture and Heritage; and written by Lincoln University economists Professor Caroline Saunders and Professor Paul Dalziel, working with Dr Catherine Savage (Ihi Research). It forms part of a series of papers published by the Treasury to generate discussion on key issues in developing the LSF and the LSF Dashboard. The Treasury developed the LSF to strengthen the quality of its policy advice through the more consistent use of wellbeing data and evidence. The LSF Dashboard pulls together a range of wellbeing indicators which inform the Treasury's advice on policy priorities for improving New Zealanders' living standards. The LSF and the LSF Dashboard are a work in progress and will continue to evolve over time. As well as culture, priority areas for further work include better reflecting Te Ao Maori and Pacific perspectives, child well-being and distributional indicators in the LSF and the Dashboard.
Keywords: 330